(untitled) (European Bison Conservation Newsletter, 2022)
The document "European Bison Species Strategic Review 2020", is very important for the further conservation of the species. This document was prepared by 32 authors from 15 countries. Its preparation was a process which took more than two years. The final version of the document was send to Glenn Plumb, chair of Bison Specialist Group IUCN, who was responsible, according to signed agreement, to publish it as “grey” literature of IUCN. On March 11, 2022 the report in PDF version has appeared on the BSG/IUCN website. The problem was that this pdf file only looks similar to “grey” literature of IUCN and after consultation with Publishing Office it became sure that the promises of the chair were not fulfilled. We, as editors of the report, decided to published it in printed version. We did not change the layout, however the ISBN number was assigned by publisher – European Bison Friends Society. Also we removed the information concerning “grey” literature. Apart from the analysis of current status of the species and recommendations for its future conservation discussed are new threats connected with Russian invasion in Ukraine and implementation of Animal Health Legislation in EU countries.